Waste Management Application through Digital System in Bengkulu City - Eko Sumartono; Siti Pahlawati; Usin Abdisyah Putra; Yudi Nugraha (Dharmakayana, 2024)
The growing population and changing consumption patterns in Bengkulu City have led to an increase in waste volume, posing environmental pollution risks affecting soil, water, and air. As a solution, the SEHATI Central Waste Bank implements a structured, community-based waste management approach that involves waste collection, sorting, processing, and recycling of both organic and inorganic waste. This initiative is supported by a digital application that streamlines waste management processes, ensures transaction transparency, and enhances incentives for participating community members. The application also provides education on the importance of 3RB (Reduce, Reuse, Recycle, Benefit), aiming to reduce waste ending up in landfills. Community service results show that the use of this digital application not only increases community participation in waste sorting and management but also effectively reduces environmental pollution. The SEHATI Waste Bank has successfully promoted environmental sustainability through a circular economy that supports sustainable waste management.